2015
DOI: 10.1016/j.aim.2015.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Modules of the 0-Hecke algebra and quasisymmetric Schur functions

Abstract: We begin by deriving an action of the 0-Hecke algebra on standard reverse composition tableaux and use it to discover 0-Hecke modules whose quasisymmetric characteristics are the natural refinements of Schur functions known as quasisymmetric Schur functions. Furthermore, we classify combinatorially which of these 0-Hecke modules are indecomposable.From here, we establish that the natural equivalence relation arising from our 0-Hecke action has equivalence classes that are isomorphic to subintervals of the weak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(87 citation statements)
references
References 51 publications
1
85
0
Order By: Relevance
“…As is the case for the dual immaculate quasisymmetric functions, but not the case for the quasisymmetric Schur functions, the modules X α for the extended Schur functions are indecomposable. We devote the remainder of the paper to establishing this fact, following the approach of [BBS`15] and [TvW15]. Let T sup α be the standard extended tableau of shape α whose entries in the ith row are the first α i integers larger than α 1`¨¨¨`αi´1 .…”
Section: Modules For Extended Schur Functionsmentioning
confidence: 99%
“…As is the case for the dual immaculate quasisymmetric functions, but not the case for the quasisymmetric Schur functions, the modules X α for the extended Schur functions are indecomposable. We devote the remainder of the paper to establishing this fact, following the approach of [BBS`15] and [TvW15]. Let T sup α be the standard extended tableau of shape α whose entries in the ith row are the first α i integers larger than α 1`¨¨¨`αi´1 .…”
Section: Modules For Extended Schur Functionsmentioning
confidence: 99%
“…More information about H n (0) and its representations can be found in [10,34], and contemporary results can be found in [6,23,24,25,26,29]. Our interest in the 0-Hecke algebra stems from the authors' previous work in the context of providing a representation-theoretic interpretation for quasisymmetric Schur functions [45].…”
Section: 2mentioning
confidence: 99%
“…The proof of the above theorem in the context of SCTs involves a lengthy verification and relies on some preliminary lemmas [45]. The techniques we need vary slightly and we discuss the differences next.…”
Section: -Hecke Modules On Spctsmentioning
confidence: 99%
See 1 more Smart Citation
“…Duchamp, Hivert, and Thibon [10] constructed the quiver of the 0-Hecke algebra H n (0) of type A n−1 and showed that H n (0) is of infinite representation type for n ≥ 4. Tewari and van Willigenburg [31,32] and König [21] studied connections between H n (0) and a new basis of quasisymmetric functions called the quasisymmetric Schur functions. After further investigation of combinatorial aspects of the representation theory of H n (0) [15,16] using the correspondence of Krob and Thibon, we recently extended this correspondence from type A to type B and type D [18,19].…”
Section: Introductionmentioning
confidence: 99%